1998
DOI: 10.1183/09031936.98.12010035
|View full text |Cite
|
Sign up to set email alerts
|

Are International Asthma Guidelines effective for low-income Brazilian children with asthma?

Abstract: The present study was designed to evaluate the effectiveness of International Asthma Guidelines in low-income asthmatic children in the city of Sao Paulo, Brazil. Fifty children with moderate or severe asthma were evaluated. Patients were evaluated before and after a 1 yr follow-up period using a pre- and post-education design with patients acting as their own controls. Parents were interviewed before and 1 yr after the programme. Most of the children were receiving inadequate medical care from their primary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
17

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 17 publications
2
20
0
17
Order By: Relevance
“…(5,18) After the medication for asthma and rhinitis came to be distributed free of charge, the proportion of patients using inhaled corticosteroid increased to 94.7%, contributing to a 94.0% decrease in hospitalizations, a value similar to that found in a case-control study involving children with asthma using inhaled corticosteroid and enrolled in an asthma education program. (19) One of the differences between the ProAR-FS and other asthma control programs is the concomitant treatment of rhinitis (providing patients with topical nasal corticosteroids), as well as the fact that the ProAR-FS serves all age brackets the care of the health team, distribution of nasal and inhaled corticosteroids, in combination with an asthma education program for patients and their relatives, was associated with a pronounced decrease in the use of health resources due to asthma in an cohort of outpatients with a history of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…(5,18) After the medication for asthma and rhinitis came to be distributed free of charge, the proportion of patients using inhaled corticosteroid increased to 94.7%, contributing to a 94.0% decrease in hospitalizations, a value similar to that found in a case-control study involving children with asthma using inhaled corticosteroid and enrolled in an asthma education program. (19) One of the differences between the ProAR-FS and other asthma control programs is the concomitant treatment of rhinitis (providing patients with topical nasal corticosteroids), as well as the fact that the ProAR-FS serves all age brackets the care of the health team, distribution of nasal and inhaled corticosteroids, in combination with an asthma education program for patients and their relatives, was associated with a pronounced decrease in the use of health resources due to asthma in an cohort of outpatients with a history of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Another group of researchers studied 50 children with moderate or severe persistent asthma between 5 and 17 years of age in the Pediatric Asthma Clinic of the Darcy Vargas Hospital, in the city of São Paulo, and found a low percentage of inhaled corticosteroid use (6%), which increased to 94% after the implementation of an educational program, which also made it possible to reduce the number of emergency room visits and the number of hospitalizations, as well as to reduce the functional severity. (27) The slightly higher percentage found in our study might be a sign that the population of hospitalized individuals presented greater disease severity, and might also indicate that, in the two public hospitals, inhaled corticosteroids were available, although inconsistently, for patients who sought treatment in their asthma outpatient clinics. In addition, there might have been greater access to the health care system in the two hospitals evaluated than that found in the above-mentioned hospital in São Paulo.…”
Section: Discussionmentioning
confidence: 55%
“…With the aim of assessing disease severity more objectively, as well as to make it possible to classify asthma as intermittent or persistent and categorize it as mild, moderate, or severe in accordance with the guidelines of the III Brazilian Consensus on Asthma Management, we used a questionnaire developed by other researchers. (18,19,27) In order to obtain a profile of the socioeconomic conditions, the maternal level of education and family income were selected, from among room, which reveals that, despite being important, preventive follow-up treatment is far from being freely accessible to low-income individuals. The suffering and the costs of hospitalization could be minimized if the access to outpatient clinics were facilitated, as well as if a national policy of follow-up treatment for patients with asthma were effectively implemented.…”
Section: Resultsmentioning
confidence: 99%
“…(23)(24)(25) Therefore, considering that free medication was made available to all patients included in the study, it is possible that the rates of compliance found here would be even lower if extrapolated to the general population.…”
Section: Discussionmentioning
confidence: 99%